2019
DOI: 10.1002/jcb.28882
|View full text |Cite
|
Sign up to set email alerts
|

Sweroside‐mediated mTORC1 hyperactivation in bone marrow mesenchymal stem cells promotes osteogenic differentiation

Abstract: This paper aims to probe into the effect of sweroside (SOS) in osteoporosis (OP) and explains mechanisms of its molecular. Applying the ovariectomized (OVX) mouse model investigates the preventive effect of SOS against postmenopausal OP after 3 months of SOS treatment (120 mg/kg/day). Using hematoxylin and eosin (HE) staining and micro computed tomography (CT) observed the morphology of OP in each group. Immunohistochemical staining (IHC) was used to examine osteoblast markers. Experiments in vitro, bone marro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…The primer sequences are listed in ESM Table 2. Western blot was performed on isolated glomeruli or cell extracts as described previously [29]. The antibodies are listed in ESM Table 1.…”
Section: Rt-pcr and Western Blotmentioning
confidence: 99%
“…The primer sequences are listed in ESM Table 2. Western blot was performed on isolated glomeruli or cell extracts as described previously [29]. The antibodies are listed in ESM Table 1.…”
Section: Rt-pcr and Western Blotmentioning
confidence: 99%
“…Therefore, the biological functions of BMSCs are vital for the homeostasis of bone. Iron is an important nutritional element for the human body [40]. However, excess iron accumulation could bring damage to cells, tissues and even organs, leading to various types of disease [41].…”
Section: Discussionmentioning
confidence: 99%
“…However, samples from Sichuan province showed a higher content of swertiamarin, and pharmacological research has revealed that this characteristic compound possesses anti-diabetic and anti-hyperlipidemic effects [28], and inhibits liver fibrosis [29]. Additionally, samples from Qinghai province have shown a higher content of sweroside, which exhibited a hepatoprotective effect [30], protective effects on osteoporosis [31], and aconitine-induced cardiac toxicity effects [32]. In view of the above reasons, it remains a challenge to estimate the herb quality of different populations.…”
Section: Discussionmentioning
confidence: 99%